Truncated trajectories, work and future: youths behind grade in senior high-school (Educação e Pesquisa, 2015)
This paper discusses the results of the quantitative step of the researchYouths behind grade: truncated trajectories of senior high-school students in the city of Rio de Janeiro. The investigation has the general purpose of learning and comprehending schooling trajectories and biographical paths of young students in senior high-school from public schools who in a grade below of they are expected. Here, we present the profile that emerges from the application of a structured questionnaire to a universe of 593 youths. The sample is exploratory and not probabilistic and was distributed among 14 schools located in the South, Downtown, West and North areas of the city of Rio de Janeiro. Young participants in the study attend classes in the so-called Young and Adult Education (EJA) and in the flow-correcting program named Autonomy. A special focus in the analysis is given to the combination of work, study and the formation of projects for the future. We have found that school drop-out creates more problems for the schooling flow than failure. Data points to the existence of an overlapping between the times of work and school in the life of these young people. Thus, there is a double effect of the work onto the students´ trajectories. If, on one hand, working and going to school mean a challenge for the continuation of studies without truncating the schooling flow, on the other hand, the experience of work creates dispositions associated with independence, the achievement of autonomy and the outlining of projects for the future.